A Novel Real-Time PCR Assay for the Rapid Detection of Virulent Streptococcus equi Subspecies zooepidemicus—An Emerging Pathogen of Swine - Kuchipudi, Suresh V.; Surendran Nair, Meera; Yon, Michele; Gontu, Abhinay; Nissly, Ruth H.; Barry, Rhiannon; Greenawalt, Denver; Pierre, Traci; Li, Lingling; Thirumalapura, Nagaraja; Tewari, Deepanker; Jayarao, Bhushan (Frontiers in Veterinary Science, 2021)
Streptococcus equi subspecies zooepidemicus, a zoonotic bacterial pathogen caused a series of outbreaks with high mortality affecting swine herds in multiple locations of the USA and Canada in 2019. Further genetic analysis revealed that this agent clustered with ATCC 35246, a S. zooepidemicus strain associated with high mortality outbreaks in swine herds of China originally reported in 1977. Rapid and accurate diagnosis is absolutely critical for controlling and limiting further spread of this emerging disease of swine. Currently available diagnostic methods including bacteriological examination and PCR assays do not distinguish between the virulent strains and avirulent commensal strains of S. zooepidemicus, which is critical given that this pathogen is a normal inhabitant of the swine respiratory tract. Based on comparative analyses of whole genome sequences of the virulent isolates and avirulent sequences, we identified a region in the SzM gene that is highly conserved and restricted to virulent S. zooepidemicus strains. We developed and validated a novel probe-based real-time PCR targeting the conserved region of SzM. The assay was highly sensitive and specific to the virulent swine isolates of Streptococcus equi subspecies zooepidemicus. No cross reactivity was observed with avirulent S. zooepidemicus isolates as well as other streptococcal species and a panel of porcine respiratory bacterial and viral pathogens. The PCR efficiency of the assay was 96.64 % and was able to detect as little as 20 fg of the bacterial DNA. We then validated the diagnostic sensitivity and specificity of the new PCR assay using a panel of clinical samples (n = 57) and found that the assay has 100% sensitivity and specificity as compared to bacteriological culture method. In summary, the PCR assay will be an extremely valuable tool for the rapid accurate detection of virulent swine S. zooepidemicus isolates and directly from clinical samples.